MOLECULAR PHYLOGENETIC ANALYSIS OF MONASCUS FUNGI BASED ON INTERNAL TRANSCRIBED SPACER REGION - SUHARNA, N; KIKUCHI, Y.; FUKATSU, T. (BIOTROPIA, 2011)
A molecular analysis of internal transcribed spacer region has been carried out to reveal the relationship among 16 strains of Monascus spp. A primer set comprised primer ITS1 and ITS4 was used to amplify this region in which they were cloned and scqucnccd. We also compared the sequence result with M. purpureus AF458473, M.ruber AF458470, M. kaoliang AF451859, M. araneous AF458471 and M. pilosus AF451856 and one outgroup species Thermoascus crustaceus U18353. The result showed that 16 Monascus spp. were divided into two large clades while M. ruber AF458470 was basically separated from all those Monascus. One of the two large clades included the seven M. purpureus strains, M. purpureus AF458473, M. araneosus AF458471 and M. kaoliang AF451859. Another large cladc included the six Monascus sp. strains which typically have whitish colonies, the three M. ruber strains and M.pilosus AF451856. However, even outstanding morphological differences possessed by several white MonascusÂ and one whitish M. purpureusÂ strain, all MonascusÂ strains were suggested to be very closely related with similarity >99% almost 100%. Although this ITS analysis could not discriminate cultural and morphological differentiation of Monascus strains studied, yet there is still little genetic variation within these strains. Key words : Molecular genetics/Monascus spp./fungi